The conclusion from one million tonnes of experience in galvanizing steel – LMAC is not a primary instigator of cracking. (December 2019) - Leighfield, C.; James, M.N.
Abstract: In the period 2000–2006 occasional instances of serious service cracking in galvanized structural steelwork were detected. At the time it was suggested that the cracks had occurred during the galvanizing process, been covered up by the zinc coating and then opened up during service. Several significant European-wide research projects were initiated to identify and understand the mechanisms that control LMAC during hot dip galvanizing. However, experience in the UK has shown that the frequency of cracking of structural steel during galvanizing is very low, and that when it does occur it is almost invariably due to known factors that influence the propensity for weld cracking and that are also influential during the galvanizing process, e.g. distortion cracking, hydrogen embrittlement and strain age embrittlement. This paper reports, for the first time, the results of a systematic attempt to examine, identify and record the possible presence and type of any pre-existing defects present in some one million tonnes of steelwork prior to the galvanizing process and their contribution to any cracking observed after galvanizing. Highlights: Reports the presence and type of any pre-existing defects present in some one million tonnes of steelwork prior to the galvanizing process Links the contribution of such defects to any cracking observed after galvanizing Only 0.033% of the total steelwork was found to be cracked, with only 0.026% of the structural steel tonnage having cracks Cracking generally associated with weld zones LMAC cannot accurately be described as a root cause of cracking during galvanizing